Stability of Caputo fractional hyperbolic systems - Arfaoui, Hassen (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.95We study the problems of well-posedness and stability  for fractional linear hyperbolic systems (FLHS) with the Caputo time-fractional derivative. First, the existence and uniqueness  are established for the global solution of the FLHS. Then we obtain some polynomial stability results for the FLHS in different Hilbert spaces. Finally, some numerical examples are presented to confirm the theoretical results.